Pengaruh Penggunaan Aplikasi Canva Terhadap Kreativitas Mahasiswa PGSD Dalam Membuat Media Pembelajaran - anisah nur afliyani; Suci Ramadhani; Jihan Humaira; Otang Kurniaman; Ningrum Melihayarti (Universitas Sains dan Teknologi Komputer, 2025)
This study aims to analyze the influence of using the Canva application on the creativity of Primary School Teacher Education (PGSD) students in developing digital learning media. This research employed a quantitative descriptive method with a correlational approach. The sample consisted of 30 PGSD students selected through purposive sampling, and data were collected using a Likert-scale questionnaire. The results showed that students’ use of Canva was categorized as very good, with a percentage of 87.33% (average score 4.37). Meanwhile, students’ creativity in creating learning media was categorized as good, with a percentage of 82.40% (average score 4.12). Students demonstrated strong abilities in operating Canva, modifying templates, and experimenting with visual elements. In terms of creativity, they were able to generate multiple ideas, adapt designs to diverse student characteristics, and pay close attention to design details. However, the ability to produce highly original